Practical prescribing. Issue 20 (5th October 1987) - Brodie, Martin J; Harrison, Ian
Abstract : This book is a practical manual for the prescriber rather than a text book. The first chapter usefully explains pharmacological terms which are used later in the book. This is followed by three sections concerned with choosing drugs. The first section gives a list of 'best buys' for common complaints, the second looks at treatment policies and the third gives basic pharmacological information to help in making choices. Side-effects and drug interactions are presented in the next two chapters in a readily accessible form. The final chapter, called 'Cautions, ' has some useful information not readily found elsewhere including data on teratogenesis and shelf-life of formulations. It also suggests which drugs we should stop using, and discusses factors to consider before using a new drug.